Pencegahan dan Penanganan Kekerasan Seksual - Winna A.A. Senandi; Thresia Hilda M. Y. Krey (JURNAL PENGABDIAN PAPUA, 2026)
The application of science and technology in the form of counseling entitled "Prevention and Handling of Sexual Violence" was conducted at Jayapura State Senior High School for Science and Language (SMA Negeri 3). The students of both high schools represent a group of school-age adolescents who must be aware of the dangers of sexual violence. Many of them still lack a clear understanding of sexual violence, and therefore, it was deemed necessary to provide counseling on the prevention and handling of sexual violence to this school-age group. Each group represented school-age adolescents. The purpose of this research and community service was to determine and understand what sexual violence is, its forms, and the various preventive measures against the dangers of sexual violence. The results of this community service were that the material presented in the counseling on the Prevention and Handling of Sexual Violence was well-received by the participants, as indicated by positive responses and thoughtful questions posed during the face-to-face counseling. Ultimately, it is hoped that education on the Prevention and Management of Sexual Violence will serve as a preventative measure to protect children from the serious threat of sexual violence.